THE PHILOXENIAN TEXT OF THE ACTS IN THE CAMBRIDGE SYRIAC MS. ADD. 2053 - Kilpatrick, George Dunbar (The journal of theological studies, 1944)
G. D. KILPATRICK; THE PHILOXENIAN TEXT OF THE ACTS IN THE CAMBRIDGE SYRIAC MS. ADD. 2053., The Journal of Theological Studies, Volume os-XLV, Issue 179-180, 1 J